Lactate-upregulation of lactate oxidation complex-related genes is blunted in left ventricle of myocardial infarcted rats - D. Gabriel-Costa; T.F. Cunha; N.A. Paixão; R.S. Fortunato; I.C.C. Rego-Monteiro; M.L.M. Barreto-Chaves; P.C. Brum (Brazilian Journal of Medical and Biological Research, 2018)
Lactate modulates the expression of lactate oxidation complex (LOC)-related genes and cardiac blood flow under physiological conditions, but its modulatory role remains to be elucidated regarding pathological cardiac stress. The present study evaluated the effect of lactate on LOC-related genes expression and hemodynamics of hearts submitted to myocardial infarction (MI). Four weeks after MI or sham operation, isolated hearts of male Wistar rats were perfused for 60 min with Na+-lactate (20 mM). As expected, MI reduced cardiac contractility and relaxation with no changes in perfusion. The impaired cardiac hemodynamics were associated with increased reactive oxygen species (ROS) levels (Sham: 19.3±0.5 vs MI: 23.8±0.3 µM), NADPH oxidase (NOX) activity (Sham: 42.2±1.3 vs MI: 60.5±1.5 nmol·h−1·mg−1) and monocarboxylate transporter 1 (mct1) mRNA levels (Sham: 1.0±0.06 vs MI: 1.7±0.2 a.u.), but no changes in superoxide dismutase (SOD), catalase, NADH oxidase (NADox), and xanthine oxidase activities. Lactate perfusion in MI hearts had no additional effect on ROS levels, NADox, and NOX activity, however, it partially reduced mct1 mRNA expression (MI-Lactate 1.3±0.08 a.u.). Interestingly, lactate significantly decreased SOD (MI-Lactate: 54.5±4.2 µmol·mg−1·min−1) and catalase (MI: 1.1±0.1 nmol·mg−1·min−1) activities in MI. Collectively, our data suggest that under pathological stress, lactate lacks its ability to modulate the expression of cardiac LOC-related genes and the perfused pressure in hearts submitted to chronic MI. Together, these data contribute to elucidate the mechanisms involved in the pathogenesis of heart failure induced by MI.